History Ahead : Stories beyond the Texas Roadside Markers - Utley, Dan K. (Book collections on Project MUSE., 2010)
In History Ahead, Utley and Beeman introduce readers to the famous (Charles Lindbergh, Will Rogers, The Big Bopper and jazz great Charlie Christian) and the not-so-famous (Elmer "Lumpy" Kleb, Don Pedro Jaramillo and Carl Morene, the "music man" of Schulenburg) who have left their marks on the history of Texas. They visit cotton gins, abandoned airfields, forgotten cemeteries, and former world War II alien detention camps to dig up the little-known and unsuspected narratives that have slipped from the knowledge of the general public.